Impact of some chemical treatments and length of storage on the storability of sugar beet - Zubi, Hussien Al; Jbawi, Entessar Al; Jeddawi, Sameer Al; Tahla, Mohammad Khair; Ismaiel, Raafat; Huniesh, Thamer Al; Aliesha, Gaidaa; Radwan, Radwan; Azzam, Hasan (International Journal of Environment, 2016)
An experiment was conducted at the Agricultural Research Center of Al Ghab, General Commission for Scientific Agricultural Research (GCSAR), Syria, to evaluate the effect of some chemical application on the sugar losses reduction, and some quality traits in 2014/2015 season. Three slaked lime concentrations of 5, 10 and 15 percent, and three concentrations of calcium chloride of 2, 4, and 6%, and a mix of 5% slaked lime with 2% calcium chloride, beside the check (no treatment) (factor C). The second factor (D) was the storage durations of 6 days, and tow varieties (Factor V) were arranged as factorial experiment in RCBD with four replications. The varieties one of them was monogerm (Vico), while the other was multigerm (Reda), they were drilled in mid November, and storage roots were harvested late August. Weight percent loss and quality of beet samples such as sugar content, total soluble solids (TSS %), and purity% were determined throughout storage period. The results of analysis of variance ANOVA showed that effect of varieties was significant for TSS (brix %), sucrose%, root weight loss (P